A Genetic Screen for Functional Partners of Condensin in Fission Yeast. Issue 2 (1st February 2014) - Robellet, Xavier; Fauque, Lydia; Legros, Pénélope; Mollereau, Esther; Janczarski, Stéphane; Parrinello, Hugues; Desvignes, Jean-Pierre; Thevenin, Morgane; Bernard, Pascal
Abstract: Mitotic chromosome condensation is a prerequisite for the accurate segregation of chromosomes during cell division, and the conserved condensin complex a central player of this process. However, how condensin binds chromatin and shapes mitotic chromosomes remain poorly understood. Recent genome-wide binding studies showing that in most species condensin is enriched near highly expressed genes suggest a conserved link between condensin occupancy and high transcription rates. To gain insight into the mechanisms of condensin binding and mitotic chromosome condensation, we searched for factors that collaborate with condensin through a synthetic lethal genetic screen in the fission yeast Schizosaccharomyces pombe . We isolated novel mutations affecting condensin, as well as mutations in four genes not previously implicated in mitotic chromosome condensation in fission yeast. These mutations cause chromosome segregation defects similar to those provoked by defects in condensation. We also identified a suppressor of the cut3-477 condensin mutation, which largely rescued chromosome segregation during anaphase. Remarkably, of the five genes identified in this study, four encode transcription co-factors. Our results therefore provide strong additional evidence for a functional connection between chromosome condensation and transcription.